An inactivated vaccine against infectious pancreatic necrosis virus in rainbow trout (Oncorhynchus mykiss). Issue 127 (August 2022) - Duan, Kaiyue; Tang, Xin; Zhao, Jingzhuang; Ren, Guangming; Shao, Yizhi; Lu, Tongyan; He, Baoquan; Xu, Liming
Abstract: Infectious pancreatic necrosis virus (IPNV), belonging to the genus Aquabirnavirus within the family Birnaviridae, causes huge economic loss to the global salmonid industry every year. Recently, outbreaks of disease caused by genogroup I IPNV were found in many rainbow trout ( Oncorhynchus mykiss ) farms worldwide. An inactivated vaccine was prepared using a genogroup I IPNV isolate with an optimized procedure as incubation with β-propanolactone (BPL) at the final concentration of 0.5% at room temperature for 48 h. The inactivated vaccine was used to immunize rainbow trout, and the protection efficiency was evaluated by viral loads determination, immune-related genes quantification, and neutralizing antibody tests. The viral loads in immunized rainbow trout were significantly decreased and the strongest antiviral effect was observed on 30 days post-immunization (d.p.i). The expression of innate immune-related genes IFN-1, and Mx-1 genes were significantly up-regulated on 3, 7, and 15 d.p.i (p < 0.05), and adaptive immune-related genes CD4, CD8, and IgM genes were significantly up-regulated on 15 and 30 d.p.i (p < 0.05). Neutralizing antibodies were firstly detected on 30 d.p.i and the highest titer was observed on 45 d.p.i, which began to decrease on 60 d.p.i, but was still significantly higher than that in negative control fish. The results indicated that the vaccine prepared in this study could stimulate the non-specific and specific immune response and provide significant immune protection to the vaccinated rainbow trout. Highlights: Genogroup I IPNV is causing huge economic loss to rainbow trout farming worldwide. A promising inactivation scheme was established by using β-propanolactone (BPL). An inactivated vaccine was prepared by using a genogroup I IPNV isolate. The vaccine could provide immune protection to IPNV challenged rainbow trout.